DAMPAK PERUBAHAN POLA PEMBELAJARAN DARING DAN LURING PADA EFEKTIVITAS BELAJAR SISWA SEKOLAH DASAR TAHUN 2021-2022 - Baron Adi Wijaya (Universitas Muria Kudus, 2023)
The purpose of this study was to determine the impact of changes in online andoffline learning patterns on the effectiveness of student learning in elementaryschools. This research is motivated by changes in online and offline learningpatterns on the effectiveness of elementary school students' learning due to thecovid 19 pandemic. Online learning is carried out by teachers without meeting inperson but students study at home by utilizing communication technology whichof course supervision and responsibility is not fully carried out by the teacher.This research is descriptive using a qualitative approach. The author is the maininstrument in obtaining detailed data. The object of this research is the studentsof SD Negeri 3 Karanggondang, Mlonggo District, Jepara Regency. The datacollections are through by interviews and questionnaires. The result of thisresearch is that online and offline learning patterns have an impact on theeffectiveness of student learning at SD Negeri 3 Karanggondang. Students ingeneral have difficulty participating in online learning because they are not usedto using technology. The students get the difficulties in accepting the materialsthat presented by the teacher. In online and offline learning, students becomedependent on their parents in doing assignments, so the teacher's assessmentcannot be a reference for learning achievement.